Rural Household Vulnerability to Poverty in South West Ethiopia: The Case of Gilgel Gibe Hydraulic Dam Area of Sokoru and Tiro Afeta Woreda (Global Journal of Human-Social Science, 2016)
This study was proposed to measure the extent of vulnerability to poverty as well the effect of socio-economic characteristics on household susceptibility to poverty using Feasible Generalized Least Squares (FGLS) estimation and logistic regression methods. The results revealed that, sizable fractions of non-poor households (51.3%) were vulnerable to poverty and 53.2 % of the sampled poor households have a probability of 50 percent and above to fall in to poverty in the near future again. Household livestock holding, crop diversification, Household head education level and household's access to credit and their exposure to idiosyncratic shocks are found to be important variables in examining the determinants of rural household vulnerability to poverty. The results suggested that since poverty and vulnerability to poverty are different signs of the same coin, policies directed towards poverty reduction need to consider not only the current poor but also the vulnerability of current non-poor households.
Keywords: poverty; poverty line; vulnerability; vulnerability to poverty; vulnerability threshold